Sistem Informasi Pengelolaan Data Nilai Siswa - Febriani ER, Riri; Sharipuddin, Sharipuddin (Jurnal Manajemen Sistem Informasi, 2023)
Analysis and design of a web-based data processing information system for student grades at SMA Negeri 12 Jambi City is a system that can provide online student activity so as to help speed and quality in delivering information. The problems that occur in processing student grades at SMA Negeri 12 Jambi City are currently using computerization but are limited to Microsoft Excel, so data redundancy still occurs which results in data inconsistency. This study aims to overcome the difficulty of conveying information related to student values, in addition to being website-based, data information can be accessed at any time. The method used in this study is the prototype method, the research tool used is UML (Unified Modeling Language). This research produces a prototype that can provide an easier solution in processing student grade data to be used as the final grade in the report card.